Flavobacterium ceti sp. nov., isolated from beaked whales (Ziphius cavirostris) - Vela Alonso, Ana Isabel; Fernández Rodríguez, Antonio Jesús; Sánchez-Porro Álvarez, Cristina; Sierra Pulpillo, Eva María; Méndez, Mariña; Arbelo Hernández, Manuel Antonio; Ventosa Ucero, Antonio; Domínguez Rodríguez, Lucas José; Fernández-Garayzábal Fernández, José Francisco (International Journal of Systematic and Evolutionary Microbiology, 2007)
Three isolates of a Gram-negative, catalase- and oxidase-positive, rod-shaped bacterium, isolated from the lung and liver of two beaked whales, were characterized by phenotypic and molecular genetic methods. Based on cellular morphology and biochemical criteria, the isolates were tentatively assigned to the family Flavobacteriaceae, although they did not appear to correspond to any recognized species. Comparative 16S rRNA gene sequencing showed that the three new isolates shared 100 % sequence similarity. The unknown bacterium was phylogenetically closely related to, but distinct from the type strains of Flavobacterium johnsoniae (93.7 % sequence similarity), Flavobacterium frigidimaris (93.4 %), Flavobacterium aquidurense (93.4 Flavobacterium hibernum (93.4 %) and Flavobacterium degerlachei (93.4 %). The novel isolates were readily distinguished from these and other related Flavobacterium species by physiological and biochemical tests. On the basis of phenotypic and phylogenetic evidence, it is proposed that the unknown isolates from whales are classified as a novel species of the genus Flavobacterium, Flavobacterium ceti sp. nov. The type strain is 454-2(T) (=CECT 7184(T) =CCUG 52969(T)). 2608 2604 2,384 Q2 SCIE